Selected measures of the impact of monetary decisions on inflation - Przybylska-Mazur, Agnieszka (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
The principal and fundamental monetary policy target is low and stable inflation, because such inflation impacts on the stability of the financial system and promotes balanced economic growth in the long term. The monetary decisions, having an impact on inflation, may be contemplated as the foundations for stronger and more balanced economic growth. A suitable monetary policy that maintains production near to potential production and that balances demand and supply shock in the economy is the necessary condition for the achievement of low and stable inflation. For analysis of the impact of monetary decisions on inflation we use the traditional vector autoregression model of reduced order of monetary policy. In this paper we present the selected measures of the impact of monetary decisions on inflation using the generalized impulse response. We present the standardized difference between the inflation rate for the scenario with the shock and the inflation rate without the occurrence of shock – the measure taking into account the cumulative impact of monetary policy impulse on inflation and the long-term impact of monetary policy impulse on inflation.
Mathematical Economics, 2012, Nr 8 (15), s. 97-110
Keywords: vector autoregression model of reduced order; impulse response function; generalized impulse response; measures of the impact of monetary policy on inflation